2008
DOI: 10.1590/s1415-47572008000300018
|View full text |Cite
|
Sign up to set email alerts
|

New soybean (Glycine max Fabales, Fabaceae) sources of qualitative genetic resistance to Asian soybean rust caused by Phakopsora pachyrhizi (Uredinales, Phakopsoraceae)

Abstract: Asian soybean rust (ASR), caused by the phytopathogenic fungi Phakopsora pachyrhizi, has caused large reductions in soybean (Glycine max) yield in most locations in Brazil where it has occurred since it was first reported in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 12 publications
2
28
0
9
Order By: Relevance
“…The obtained segregation pattern in the F 2 generations of each cross also supported the hypothesis that each new source carries a single dominant gene controlling resistance. The soybean breeding line BR01-18437, studied by Pierozzi et al (2008), probably received its resistant gene from PI 203398 (Abura), which was used as high protein genetic source. However, the gene from BR01-18437 is recessive, while the gene from PI 203398 studied here is dominant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained segregation pattern in the F 2 generations of each cross also supported the hypothesis that each new source carries a single dominant gene controlling resistance. The soybean breeding line BR01-18437, studied by Pierozzi et al (2008), probably received its resistant gene from PI 203398 (Abura), which was used as high protein genetic source. However, the gene from BR01-18437 is recessive, while the gene from PI 203398 studied here is dominant.…”
Section: Resultsmentioning
confidence: 99%
“…The observed segregation pattern, 13 resistant to 3 susceptible, indicated that its resistant gene is recessive or does not express dominance when crossed with PI 230970 and PI 459025. Recessive ASR-resistance genes have been fi rst reported in the soybean line BR01-18437 (Pierozzi et al, 2008), andthen in PI 200456 andPI 224270 (Calvo et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os genótipos testados e seus respectivos Grupos de Maturidade Relativa (GMR) foram: 'BRS 291RR' (6.6), 'NK 7059RR' (6.2), 'BRS 245RR' (7.5), 'BRS Favorita RR' (7.9), 'BRS 239' (6.9), 'BRS 320' (6.2), 'BR 02-04844' (7.2) e 'BRSGO 7560' (7.4). Destes, apenas a cultivar 'NK 7059RR' e a linhagem 'BR 02-04844' apresentam tipo de crescimento indeterminado, e a cultivar 'BRSGO 7560' é a única que possui gene de resistência monogênica, a qual é oriunda da fonte 'BR01-18437' (PIEROZZI et al, 2008).…”
Section: Methodsunclassified
“…portadores de genes maiores, ou ainda resistências ditas verticais, tem sido um grande desafio para a pesquisa (CALVO et al, 2008;PIEROZZI et al, 2008;MAPHOSA et al, 2013).…”
Section: Introductionunclassified